The legal status of shipping orders and the shipping manifest as documents of title under the hague rules in Malaysia / Dr. Irwin Uj Ooi - Uj Ooi, Irwin (Faculty of Administratron and Law, 2004)
There has been a dearth of reported shipping law cases in Peninsular Malaysia since the mid to late 1990s, and this is a trend that persists until today. Only a handful of cases are now reported annually in the local law reports and development of shipping law via the common law of Malaysia has come almost to a standstill in the Peninsular. Therefore, two recent decisions generated an unusually high degree of excitement among the marine legal fraternity as the Malaysian judiciary was presented with two opportunities to express views on the legal status of two documents used in local commercial shipping. Both these cases were heard in the High Courts of Kuching and Miri respectively, thus preserving Borneo's reputation as a hotbed of litigation on shipping matters in Malaysia. The first part of this article deals with the legal recognition of shipping orders as a document of title, and the second part concerns the shipping manifest.